2015
DOI: 10.1007/s10508-015-0557-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Psychological Adjustment Among Transsexuals in Spain

Abstract: This study examined the sociodemographic characteristics and the psychological adjustment of transsexuals in Andalusia (Spain), and also analyzed the differences between female-to-male (FtM) and male-to-female (MtF) transsexuals. The sample included 197 transsexuals (101 MtF and 96 FtM) selected from those who visited the Transsexual and Gender Identity Unit at the Carlos Haya Hospital in Malaga between 2011 and 2012. Our analyses indicated that MtF transsexuals were more likely to have lower educational level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 59 publications
0
11
0
5
Order By: Relevance
“…Eight other studies that used structured clinical interviews for data collection (Colizzi et al 2015;Gómez-Gil et al 2009;Guzmán-Parra et al 2015;Haraldsen & Dahl 2000;Hepp et al 2005;Madeddu et al 2009;Mazaheri Meybodi et al 2014a,b) reported generally similar results (see Supplemental Table 1): Most found about a 30-40% prevalence of current comorbid psychopathology and about a 50-80% prevalence of lifetime comorbid psychopathology in adults with GD, including a 20-60% prevalence of personality disorders. Another large study by Landén et al (1998), which used data from Swedish national registries-the same method that Dhejne et al (2011) subsequently employed-reported similar results, as did three smaller studies by Miach et al (2000) and De Cuypere et al (1995,2006), all of which found a high prevalence of associated psychopathology despite the use of unstructured clinical interviews.…”
Section: Increased Prevalence Of Associated Psychopathologymentioning
confidence: 78%
“…Eight other studies that used structured clinical interviews for data collection (Colizzi et al 2015;Gómez-Gil et al 2009;Guzmán-Parra et al 2015;Haraldsen & Dahl 2000;Hepp et al 2005;Madeddu et al 2009;Mazaheri Meybodi et al 2014a,b) reported generally similar results (see Supplemental Table 1): Most found about a 30-40% prevalence of current comorbid psychopathology and about a 50-80% prevalence of lifetime comorbid psychopathology in adults with GD, including a 20-60% prevalence of personality disorders. Another large study by Landén et al (1998), which used data from Swedish national registries-the same method that Dhejne et al (2011) subsequently employed-reported similar results, as did three smaller studies by Miach et al (2000) and De Cuypere et al (1995,2006), all of which found a high prevalence of associated psychopathology despite the use of unstructured clinical interviews.…”
Section: Increased Prevalence Of Associated Psychopathologymentioning
confidence: 78%
“…Среди группы MtF характерен более поздний возраст обращения, при одинаковом с FtM возрасте самоидентификации себя в противоположном гендере. Это соотносится с мировой статистикой (Испания, Италия, Бразилия) [20,28,29]. Недавно английскими учеными была проведена работа, где исследовалась группа транссексуалов старшего возраста (50 лет и более), впервые обратившихся за назначением гормональной терапии.…”
Section: Discussionunclassified
“…14e16 Studies in the GD population seeking sex reassignment showed that the most prevalent disorders are affective and anxiety disorders. 11,12,17 Moreover, other studies report that hormonal treatment seems to improve this psychiatric morbidity 18e20 and also reduces perceived stress and cortisol response. 21 Regarding the prevalence of current social anxiety disorder (SAD) (last 30 days) in studies of primary care patients within the general population, a prevalence between 2%e4.2% has been reported.…”
Section: Introductionmentioning
confidence: 99%